2019
DOI: 10.1103/physrevlett.122.218501
|View full text |Cite
|
Sign up to set email alerts
|

Continuously Sheared Granular Matter Reproduces in Detail Seismicity Laws

Abstract: We introduce a shear experiment that quantitatively reproduces the main laws of seismicity. By continuously and slowly shearing a compressed monolayer of disks in a ring-like geometry, our system delivers events of frictional failures with energies following a Gutenberg-Richter law. Moreover foreshocks and aftershocks are described by Omori laws and inter-event times also follow exactly the same distribution as real earthquakes, showing the existence of memory of past events. Other features of real earthquakes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 44 publications
5
53
0
Order By: Relevance
“…We find that the ensemble probability density function of kinetic energies PðEÞ shows a robust power-law decay over more than three decades in E ( Fig. 2a): PðEÞ $ 1=E ϵ , where ϵ ¼ 1 þ ðb=1:5Þ ¼ 1:6 ± 0:1; consistent with the Gutenberg-Richter law for the distribution of earthquake amplitudes 28 , and is close to the value of ϵ obtained in other experiments 2,6,10 . The value of the Gutenberg-Richter exponent b for our system (¼ 0:90 ± 0:15) is very close to the most accepted value for earthquakes (b $ 1), but slightly greater than the reported values for other fracture experiments (b $ 0:60) 8,9,11 .…”
Section: R Dsupporting
confidence: 88%
See 1 more Smart Citation
“…We find that the ensemble probability density function of kinetic energies PðEÞ shows a robust power-law decay over more than three decades in E ( Fig. 2a): PðEÞ $ 1=E ϵ , where ϵ ¼ 1 þ ðb=1:5Þ ¼ 1:6 ± 0:1; consistent with the Gutenberg-Richter law for the distribution of earthquake amplitudes 28 , and is close to the value of ϵ obtained in other experiments 2,6,10 . The value of the Gutenberg-Richter exponent b for our system (¼ 0:90 ± 0:15) is very close to the most accepted value for earthquakes (b $ 1), but slightly greater than the reported values for other fracture experiments (b $ 0:60) 8,9,11 .…”
Section: R Dsupporting
confidence: 88%
“…To cut through the complexity of such a large-scale reorganization phenomenon, there have been significant recent efforts in mimicking earthquakes in controlled laboratory experiments by studying the deformation and failure in various solid materials under external loads. These include fracture of rock samples under compression [1][2][3][4][5][6] , fracture of artificial rock of sintered polystyrene beads 7 , compression of mesoporous silica ceramics 8 , avalanches in wood compression 9 and stick-slip instabilities under shear in a twodimensional assembly of polymer disks 10 . A recent study 11 demonstrates that charcoal samples damped with ethanol show avalanche events similar to earthquakes due to the internal stresses generated from ethanol evaporation.…”
mentioning
confidence: 99%
“…In the purpose of exploring the deformation regimes of a natural fault that accommodate slip through a wide range of micro to macro‐ruptures, this experimental set‐up offers interesting advantages: (1) the annular geometry allows sliding over very large distances (up to meters), hence the total imposed slip can be several times the fault's length, implying that the fault goes through several loading/seismic cycles; (2) the fault enters a slowly evolving, quasi steady‐state; (3) because of the geometry of the experiment and the boundary conditions applied the normal stress is low, resulting only from geometrical mismatch between the two sides of the fault; (4) a wide range of torque drops is indeed observed, so that a non‐periodic, complex deformation is the norm. Similar features have also been obtained for granular systems (e.g., Hartley & Behringer, ; Lherminier et al, ; Miller et al, ), but we here reproduce them for a brittle, cohesive medium.…”
Section: Introductionsupporting
confidence: 84%
“…In previous studies, it was confirmed that the MS parameters, such as amplitude, event number and frequency, which could reflect the quantity, size and direction of microcrack propagation, had a great relevance on damage degree of coal and rock [20][21][22][23]. The actual MS signals contain a great amount of noise whose interference often results in the difficulty of the signal processing.…”
Section: Introductionmentioning
confidence: 86%
“…where, K III is the stress intensity factor of mode-III crack and ν is the Poisson's ratio. According to Formulas (21)- (23), with the increase of stress, the energy release rate increases, which can lead to the widening of MS signals spectrum. This was consistent with experimental results that the high-frequency and low-frequency signals both increased and the band width widened at the late loading stage.…”
Section: The Intrinsic Reason Of Spectrum Evolution Of Ms Signalsmentioning
confidence: 99%